Nano cerium-zirconium oxide as well as preparation method and application thereof

By using water-soluble polyamide auxiliary adsorption materials, the formation and dispersion of cerium-zirconium composite hydroxides are promoted, and the problems of long preparation cycle, high cost and insufficient performance in the prior art are solved, and the preparation of cerium-zirconium oxides with high specific surface area and wide pore size distribution is achieved to meet the needs of the new generation of emission regulations.

CN119612587APending Publication Date: 2025-03-14DONGFENG MOTOR GRP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411195483.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing cerium-zirconium-based composite oxygen storage material preparation technology has long preparation cycles, high production costs, easy production of industrial wastewater, affect industrial production, and low specific surface area of ​​the product after high-temperature aging, which cannot meet the performance requirements of the new generation of emission regulations for oxygen storage materials.

Method used

Water-soluble polyamide is used as auxiliary adsorption material to form PAM-rare earth metal complexes through the coordination adsorption effect on rare earth metal cations, promote the formation and dispersion of Ce and Zr hydroxide colloids, reduce the collapse of crystal pore structure caused by high-temperature roasting, and improve the specific surface area and pore size distribution width.

Benefits of technology

It has achieved a shortening of the preparation cycle, low-cost and easy-to-access auxiliary materials, safe and environmentally friendly, and obtained cerium-zirconium composite oxides with high specific surface area, large pore capacity and wide pore size distribution, meeting the requirements of the new generation of emission regulations for the performance of oxygen storage materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612587A_ABST
    Figure CN119612587A_ABST
Patent Text Reader

Abstract

The invention relates to a nano cerium-zirconium oxide as well as a preparation method and application thereof, and belongs to the technical field of automobile exhaust purification. Water-soluble polyamide is used as an auxiliary adsorption material, so that the utilization rate of rare earth metal elements and the dispersity of the rare earth metal elements in a final product are improved, and the material cost is reduced and the highest oxide high-temperature thermal stability is improved. Meanwhile, adsorption points of rare earth metal elements in the PAM-rare earth metal complex play a role in heterogeneous nucleation, and crystal nucleus formation can be promoted; and the water-soluble PAM is beneficial to improving the content of substances around crystal nucleuses, accelerating the crystallization process and obtaining large-size crystals, and is beneficial to shortening the crystallization aging time. Hydrophilic groups and hydrophobic groups exist in water-soluble PAM molecules at the same time, so that the water surface tension can be reduced, the dispersity of hydroxide colloid in a precipitation flocculating constituent is improved, and the reduction of the specific surface area caused by agglomeration is reduced; meanwhile, a PAM molecular chain can slow down collapse of a crystal pore channel structure caused by water loss in the process of roasting hydroxide colloid into oxide at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of automobile exhaust purification, and in particular to a nano cerium-zirconium oxide and a preparation method and application thereof. Background Art

[0002] Exhaust treatment for gasoline and hybrid vehicles is the key to pollution prevention and control. Three-way catalysts (TWCs) can convert the three main automobile exhaust pollutants, HC, CO and NOx, into harmless H2O, CO2 and N2. TWCs consist of two components: a honeycomb carrier and a catalytic coating. Among them, the cerium-zirconium-based composite oxygen storage material is a key part of the catalytic coating, which plays a role in dispersing active components and widening the air-fuel ratio window. Its preparation technology is one of the core technologies of TWCs.

[0003] There are many preparation technologies for cerium-zirconium-based composite oxygen storage materials disclosed at present. The preparation path is to prepare a salt solution containing Ce, Zr and rare earth elements in a preset proportion, then add an alkaline solvent by titration to obtain a hydroxide precipitate, and finally calcine the precipitate at high temperature to obtain a cerium-zirconium-based composite oxygen storage material. In the preparation process, how to improve the dispersion of hydroxide precipitates and reduce agglomeration, promote the uniform dispersion of oxides to form a solid solution, and reduce the specific surface loss caused by high-temperature calcination is the key to the preparation technology. For example, in the prior art, Chinese invention patent application CN106824163B discloses a method for preparing composite oxides by co-precipitation, measuring the precursors of each oxide and preparing a precursor solution with a concentration of 5 to 10%; then titrating and aging with ammonia water, or an alkaline solution composed of ammonia water and ammonium carbonate, adding polyethylene glycol solution or lauric acid for dispersion, filtering, washing to neutrality to obtain a filter cake, and finally warm calcining to obtain a composite oxide. This technology uses polyethylene glycol as a dispersant and lauric acid as a surfactant. After the final product is calcined at 1000℃ for 5h, the specific surface area can still be maintained at 91~95m 2 / g, pore volume 0.44~0.51ml / g, average pore radius 8.0~10.5nm. Chinese invention patent application CN102407100B discloses a method for preparing composite oxides by template method, wherein nitrates of cerium, rare earth and zirconium are dissolved in water to obtain a salt solution, which is mixed with Tween-80 and n-C8H17OH to obtain lamellar liquid crystal A; ammonia water is mixed with Tween-80 and n-C8H17OH to obtain lamellar liquid crystal B; lamellar liquid crystal B is added to lamellar liquid crystal A to obtain an oxygen storage material precursor, which is dried and calcined to prepare a rare earth oxygen storage material. This technology uses Tween-80 as a dispersant and n-C8H17OH as a surfactant. The prepared product has a specific surface area ≥90m 2 / g, particle size ≤100nm, specific surface area ≥30m after calcination at 1000℃ for 4h 2 / g. Chinese invention patent application CN101637721B discloses a method for preparing composite oxides by microsphere method, wherein a precipitant is added to a protective agent, a mixed metal salt solution and an active polystyrene microsphere emulsion, and a porous yttrium-cerium-zirconium solid solution is obtained after reaction at room temperature, aging at high temperature, washing and drying, and high temperature calcination. Polyethylene glycol is used as a dispersant and a polystyrene microsphere emulsion is used as a carrier. The prepared product is calcined at 400-500°C for 2-3 hours, and the specific surface area is 100-150m 2 / g, pore size is 7-10nm; aging at 900-1000℃ for 4-5h, specific surface area is 35-60m 2 / g. Chinese invention patent application CN108970602B discloses a sol-gel preparation technology, in which a salt solution containing cerium, zirconium, praseodymium, aluminum and scandium ions and an amino acid are reacted in an organic solvent to obtain a sol; the sol and a slow-release solution (with a controlled pH value) are mixed, hydrolyzed and polycondensed to obtain a gel; the gel is heated to a spontaneous combustion temperature, and the powder after combustion is collected to obtain an oxygen storage material. The role of the sol and gel is also to promote dispersion and reduce agglomeration during high-temperature calcination to a great extent. The specific surface area of ​​the prepared product can reach 88.6m 2 / g, after calcination at 1200℃ for 4h, it can maintain 48.5m 2 / g.

[0004] It can be seen that the existing cerium-zirconium-based composite oxygen storage material preparation technology has the following shortcomings: long preparation cycle, high production cost, easy to generate industrial wastewater, affecting industrial production; or there is a relatively low comparative area of ​​the product after high-temperature aging, and it cannot meet the performance requirements of the new generation of emission regulations for oxygen storage materials. Summary of the invention

[0005] The present application provides a nano cerium-zirconium oxide and a preparation method and application thereof, which has the advantages of relatively short preparation cycle, cheap and easy to obtain auxiliary materials, safety and environmental protection, etc. The prepared cerium-zirconium composite oxide has the texture characteristics of high specific surface area, large pore volume and wide pore size distribution.

[0006] In a first aspect, the present application provides a method for preparing nano cerium zirconium oxide, the method comprising:

[0007] obtaining an auxiliary adsorption material solution, wherein the auxiliary adsorption material comprises polyamide;

[0008] Dispersing a rare earth element salt in the auxiliary adsorption material solution to obtain a first solution;

[0009] reacting a mixed solution of cerium salt and zirconium salt, an alkali solution and the first solution to obtain cerium-zirconium composite hydroxide floccules;

[0010] The cerium-zirconium composite hydroxide floccules are baked and calcined to obtain nano-cerium-zirconium oxide.

[0011] As an optional embodiment, the polyamide includes anionic polyamide.

[0012] As an optional implementation manner, the mass concentration of the auxiliary adsorption material in the auxiliary adsorption material solution is 0.2% to 0.5%.

[0013] As an optional implementation, the rare earth element salt includes yttrium salt and lanthanum salt.

[0014] As an optional embodiment, the yttrium salt comprises yttrium nitrate; and / or

[0015] The lanthanum salt comprises lanthanum nitrate; and / or

[0016] The cerium salt comprises cerium nitrate; and / or

[0017] The zirconium salt comprises zirconium nitrate; and / or

[0018] The molar ratio of the metal elements Ce, Zr, Y and La in the cerium salt, zirconium salt, yttrium salt and lanthanum salt is (22-24): (40-42): (4-5): (2-3).

[0019] As an optional embodiment, the total mass concentration of the metal elements Y and La in the first solution is 1% to 2%; and / or

[0020] The total mass concentration of the metal elements Ce and Zr in the mixed solution of the cerium salt and the zirconium salt is 10% to 20%.

[0021] As an optional embodiment, the alkali solution includes at least one of an aqueous ammonia solution and an alkali metal solution; and / or

[0022] The mixing reaction is carried out by titration; and / or

[0023] The pH value of the whole system during the mixed reaction is 8.5 to 9.5; and / or

[0024] The volume of the mixed solution of cerium salt and zirconium salt is 10 to 20 times the volume of the first solution.

[0025] In a second aspect, the present application provides a nano-cerium-zirconium oxide, which is prepared by the method provided in the first aspect.

[0026] As an optional embodiment, the nano cerium zirconium oxide includes CeO2, ZrO2, Y2O3 and La2O3, and the mass ratio of CeO2, ZrO2, Y2O3 and La2O3 is (35-45): (45-55): (5-10): (5-10).

[0027] In a third aspect, the present application provides a three-way catalyst, wherein the three-way catalyst comprises a catalytic coating, and the catalytic coating comprises the nano cerium zirconium oxide provided in the second aspect.

[0028] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0029] The method provided in the embodiment of the present application uses water-soluble polyamide as an auxiliary adsorption material, and utilizes its coordination adsorption effect on rare earth metal cations to first capture rare earth metal cations with a low content to form PAM-rare earth metal complexes, and then secondary adsorbs to form Ce and Zr hydroxide colloids, thereby improving the utilization rate of rare earth metal elements and dispersibility in the final product, which is beneficial to reducing material costs and improving the high-temperature thermal stability of the highest oxide. At the same time, in the formation and crystallization process of Ce and Zr hydroxides, the adsorption points of rare earth metal elements in the PAM-rare earth metal complex play a heterogeneous nucleation role, which can promote the formation of crystal nuclei; and the water-soluble PAM has an adsorption effect on the hydroxide colloid in the solution, which helps to increase the content of substances around the crystal nucleus, accelerate the crystallization process and obtain larger crystals, which is beneficial to shorten the crystallization aging time. In addition, the presence of hydrophilic groups and hydrophobic groups in the water-soluble PAM molecules can reduce the surface tension of water, improve the dispersibility of hydroxide colloids in precipitated flocs, and reduce the reduction in specific surface area caused by agglomeration; at the same time, the network structure formed between the PAM molecular chains helps to protect the colloid, and to a certain extent can slow down the collapse of the crystal pore structure caused by the loss of water in the process of high-temperature roasting of hydroxide colloids into oxides, resulting in a reduction in surface area and pore size. In addition, the water-soluble PAM itself has a water purification effect, which can eliminate pollutants in industrial wastewater generated in the production process of the present invention, and has environmental advantages. In summary, the method has the advantages of relatively short preparation cycle, low-cost and easy-to-obtain auxiliary materials, safety and environmental protection, and the preparation of cerium-zirconium composite oxides has the texture characteristics of high specific surface area, large pore volume and wide pore size distribution. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0031] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0032] Figure 1 A flowchart of the method provided in the embodiment of the present application. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0035] Figure 1 A flow chart of the method provided in the embodiment of the present application is as follows: Figure 1 As shown, the present application embodiment provides a method for preparing nano cerium zirconium oxide, the method comprising:

[0036] S1. Obtaining an auxiliary adsorption material solution, wherein the auxiliary adsorption material comprises polyamide;

[0037] Specifically, in this embodiment, the auxiliary adsorption material solution can be prepared by slowly adding polyamide PAM powder into deionized water at a stirring speed of 500 to 1000 r / min and stirring for 1 to 1.5 hours, the water temperature is controlled at 30 to 60° C., and the mass concentration of polyamide PAM in the final solution is 0.2 to 0.5%.

[0038] In some embodiments, the polyamide comprises anionic polyamide. Furthermore, the mass concentration of the auxiliary adsorption material in the auxiliary adsorption material solution is 0.2% to 0.5%.

[0039] Illustratively, the mass concentration of the auxiliary adsorption material in the auxiliary adsorption material solution may be 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45% or 0.5%, etc., and may also be any value within the range of 0.2% to 0.5%.

[0040] S2. dispersing the rare earth element salt in the auxiliary adsorption material solution to obtain a first solution;

[0041] In some embodiments, the rare earth element salt includes yttrium salt and lanthanum salt. The yttrium salt includes yttrium nitrate; the lanthanum salt includes lanthanum nitrate. The yttrium salt and lanthanum salt are preferably added to the auxiliary adsorption material solution in the form of aqueous solution.

[0042] In some embodiments, the total mass concentration of the metal elements Y and La in the first solution is 1% to 2%.

[0043] Exemplarily, the total mass concentration of the metal elements Y and La in the first solution can be 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%, etc., and it can also be any value in the range of 1% to 2%.

[0044] S3. The mixed solution of cerium salt and zirconium salt, alkali solution and the first solution are reacted to obtain cerium zirconium composite hydroxide floccules;

[0045] Specifically, in this embodiment, the mixed solution of cerium salt and zirconium salt and alkali solution are titrated into the first solution at room temperature to obtain a cerium-zirconium composite hydroxide flocculant solution, and after the titration, the solution is aged at 90-95° C. for 3-4 hours, and then cooled to room temperature, and filtered to separate the cerium-zirconium composite hydroxide flocculants. During the titration, the stirring speed of the solution is maintained at 300-400 rpm.

[0046] In some embodiments, the cerium-zirconium composite hydroxide flocs can also be purified, and the purification process can be: washing the cerium-zirconium composite hydroxide flocs with an ammonium salt aqueous solution, and dehydrating to obtain purified cerium-zirconium composite hydroxide flocs. The ammonium salt aqueous solution is preferably an ammonium carbonate solution, and the washing process conditions are stirring at 50-80° C. and 200-300 rpm for 1-2 hours.

[0047] In some embodiments, the cerium salt comprises cerium nitrate; and the zirconium salt comprises zirconium nitrate.

[0048] In some embodiments, the total mass concentration of the metal elements Ce and Zr in the mixed solution of the cerium salt and the zirconium salt is 10% to 20%.

[0049] Exemplarily, the total mass concentration of the metal elements Ce and Zr in the mixed solution of the cerium salt and the zirconium salt can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., and it can also be any value in the range of 10% to 20%.

[0050] In some embodiments, the molar ratio of the metal elements Ce, Zr, Y and La in the cerium salt, zirconium salt, yttrium salt and lanthanum salt is (22-24): (40-42): (4-5): (2-3).

[0051] Illustratively, the molar ratio of the metal elements Ce, Zr, Y and La in cerium salts, zirconium salts, yttrium salts and lanthanum salts can be 22:41:4.5:2.5, 23:41:4.5:2.5, 24:41:4.5:2.5, 23:40:4.5:2.5, 23:42:4.5:2.5, 23:41:4:2.5, 23:41:5:2.5, 23:41:4.5:2 or 23:41:4.5:3, etc., and it can also be any value within the range of (22-24):(40-42):(4-5):(2-3).

[0052] In some embodiments, the alkali solution includes at least one of an aqueous ammonia solution and an alkali metal solution.

[0053] In some embodiments, the mixing reaction is performed by titration. Furthermore, the pH value of the entire system during the mixing reaction is 8.5 to 9.5.

[0054] Illustratively, the pH value of the entire system during the mixing reaction can be 8.5, 8.6, 8.7, 8.8, 8.9, 9, 9.1, 9.2, 9.3, 9.4 or 9.5, etc., and can also be any value within the range of 8.5 to 9.5.

[0055] In some embodiments, the volume of the mixed solution of cerium salt and zirconium salt is 10 to 20 times the volume of the first solution.

[0056] Illustratively, the volume of the mixed solution of cerium salt and zirconium salt can be 10 times, 11 times, 12 times, 13 times, 14 times, 15 times, 16 times, 17 times, 18 times, 19 times or 20 times the volume of the first solution, etc., and it can also be any value within the range of 10 to 20 times.

[0057] S4. baking and calcining the cerium-zirconium composite hydroxide floccules to obtain nano-cerium-zirconium oxide.

[0058] Specifically, in this embodiment, the cerium-zirconium composite hydroxide floccules are baked at 200-300° C. for 2-3 hours to decompose and remove organic matter and water; and then calcined at 600-800° C. for 3-5 hours to obtain nano-cerium-zirconium oxide.

[0059] This method uses water-soluble polyamide as an auxiliary adsorption material, and utilizes its coordination adsorption effect on rare earth metal cations to first capture rare earth metal cations with a low content to form PAM-rare earth metal complexes, and then secondary adsorption to form Ce and Zr hydroxide colloids, thereby improving the utilization rate of rare earth metal elements and their dispersibility in the final product, which is beneficial to reducing material costs and improving the high-temperature thermal stability of the highest oxide. At the same time, during the formation and crystallization of Ce and Zr hydroxides, the adsorption points of rare earth metal elements in the PAM-rare earth metal complex play a heterogeneous nucleation role, which can promote the formation of crystal nuclei; and the water-soluble PAM has an adsorption effect on the hydroxide colloid in the solution, which helps to increase the content of substances around the crystal nucleus, accelerate the crystallization process and obtain larger crystals, which is beneficial to shorten the crystallization aging time. In addition, the presence of both hydrophilic and hydrophobic groups in the water-soluble PAM molecules can reduce the surface tension of water, improve the dispersibility of the hydroxide colloid in the precipitated flocs, and reduce the reduction in specific surface area caused by agglomeration; at the same time, the network structure formed between the PAM molecular chains helps to protect the colloid, and to a certain extent can slow down the collapse of the crystal pore structure caused by the loss of water in the process of the hydroxide colloid being calcined into oxides at high temperature, resulting in a reduction in surface area and pore size. In addition, the water-soluble PAM itself has a water purification function, which can eliminate pollutants in the industrial wastewater generated in the production process of the present invention, and has environmental advantages.

[0060] In summary, this method has the advantages of relatively short preparation cycle, cheap and easy to obtain auxiliary materials, safety and environmental protection, etc. The prepared cerium-zirconium composite oxide has the texture characteristics of high specific surface area, large pore volume and wide pore size distribution.

[0061] Based on a general inventive concept, an embodiment of the present application further provides a nano-cerium-zirconium oxide, which is prepared by the method provided above.

[0062] The nano cerium-zirconium oxide is prepared based on the above method. The specific steps of the method can refer to the above embodiment. Since the nano cerium-zirconium oxide adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be repeated here.

[0063] In some embodiments, the nano cerium zirconium oxide includes CeO2, ZrO2, Y2O3 and La2O3, and the mass ratio of CeO2, ZrO2, Y2O3 and La2O3 is (35-45): (45-55): (5-10): (5-10).

[0064] For example, the mass ratio of CeO2, ZrO2, Y2O3 and La2O3 can be 35:50:7:7, 36:50:7:7, 37:50:7:7, 38:50:7:7, 39:50:7:7, 40:50:7:7, 41:50:7:7, 42:50:7:7, 43:50:7:7, 44:50:7:7, 45:50:7:7, 40:45:7:7, 40:46:7:7, 40:47:7:7, 40:48:7:7, 40:49:7:7, 41:50:7:7, 42:50:7:7, 43:50:7:7, 44:50:7:7, 45:50:7:7, 46:7:7, 47:7:7, 48:7:7, 49:7:7, 49:7:7 0:51:7:7, 40:52:7:7, 40:53:7:7, 40:54:7:7, 40:55:7:7, 40:50:5:7, 40:50:6:7, 40:50:8:7, 40:50:9:7, 40:50:10:7, 40:50:7:5, 40:50:7:6, 40:50:7:8, 40:50:7:9 or 40:50:7:10, etc. It can also be any value in the range of (35-45):(45-55):(5-10):(5-10).

[0065] Based on a general inventive concept, an embodiment of the present application further provides a three-way catalyst, wherein the three-way catalyst comprises a catalytic coating, and the catalytic coating comprises the nano cerium-zirconium oxide provided above.

[0066] The three-way catalyst is realized based on the above-mentioned nano cerium zirconium oxide. The specific content of the nano cerium zirconium oxide can be referred to the above-mentioned embodiment. Since the three-way catalyst adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0067] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0068] Example 1

[0069] A nano cerium zirconium oxide, the preparation process is as follows:

[0070] A. Weigh the corresponding weights of soluble cerium salt (cerium nitrate), soluble zirconium salt (cerium nitrate), soluble yttrium salt (yttrium nitrate), and soluble lanthanum salt (lanthanum nitrate) according to the molar ratio of metal elements of 22:40:4:2;

[0071] B. Firstly, dissolve water-soluble polyamide in deionized water, then dissolve yttrium salt and lanthanum salt in the polyamide aqueous solution to prepare PAM-Y / La solution. Dissolve cerium salt and zirconium salt in deionized water to prepare Ce / Zr solution.

[0072] C. The Ce / Zr solution is titrated with alkali solution at room temperature to react with the PAM-Y / La solution to prepare a cerium-zirconium composite hydroxide flocculant solution; after the titration, the solution is aged at 92° C. for 3.5 h; the solution is then cooled to room temperature and filtered to separate the cerium-zirconium composite hydroxide flocculant.

[0073] D. Washing the cerium-zirconium composite hydroxide flocs with an ammonium salt aqueous solution and dehydrating the flocs to obtain purified cerium-zirconium composite hydroxide flocs.

[0074] E. Bake at 250°C for 2.5 hours to decompose and remove organic matter and water; then calcine at 700°C for 4 hours to obtain the composite oxide.

[0075] Example 2

[0076] A nano cerium zirconium oxide, the preparation process is as follows:

[0077] A. Weigh the corresponding weights of soluble cerium salt (cerium nitrate), soluble zirconium salt (cerium nitrate), soluble yttrium salt (yttrium nitrate), and soluble lanthanum salt (lanthanum nitrate) according to the molar ratio of metal elements of 23:41:4.5:2.5;

[0078] B. Firstly, dissolve water-soluble polyamide in deionized water, then dissolve yttrium salt and lanthanum salt in the polyamide aqueous solution to prepare PAM-Y / La solution. Dissolve cerium salt and zirconium salt in deionized water to prepare Ce / Zr solution.

[0079] C. The Ce / Zr solution is titrated with alkali solution at room temperature to react with the PAM-Y / La solution to prepare a cerium-zirconium composite hydroxide flocculant solution; after the titration, the solution is aged at 92° C. for 3.5 h; the solution is then cooled to room temperature and filtered to separate the cerium-zirconium composite hydroxide flocculant.

[0080] D. Washing the cerium-zirconium composite hydroxide flocs with an ammonium salt aqueous solution and dehydrating the flocs to obtain purified cerium-zirconium composite hydroxide flocs.

[0081] E. Bake at 250°C for 2.5 hours to decompose and remove organic matter and water; then calcine at 700°C for 4 hours to obtain the composite oxide.

[0082] Example 3

[0083] A nano cerium zirconium oxide, the preparation process is as follows:

[0084] A. Weigh the corresponding weights of soluble cerium salt (cerium nitrate), soluble zirconium salt (cerium nitrate), soluble yttrium salt (yttrium nitrate), and soluble lanthanum salt (lanthanum nitrate) according to the molar ratio of metal elements of 24:42:5:3;

[0085] B. Firstly, dissolve water-soluble polyamide in deionized water, then dissolve yttrium salt and lanthanum salt in the polyamide aqueous solution to prepare PAM-Y / La solution. Dissolve cerium salt and zirconium salt in deionized water to prepare Ce / Zr solution.

[0086] C. The Ce / Zr solution is titrated with alkali solution at room temperature to react with the PAM-Y / La solution to prepare a cerium-zirconium composite hydroxide flocculant solution; after the titration, the solution is aged at 92° C. for 3.5 h; the solution is then cooled to room temperature and filtered to separate the cerium-zirconium composite hydroxide flocculant.

[0087] D. Washing the cerium-zirconium composite hydroxide flocs with an ammonium salt aqueous solution and dehydrating the flocs to obtain purified cerium-zirconium composite hydroxide flocs.

[0088] E. Bake at 250°C for 2.5 hours to decompose and remove organic matter and water; then calcine at 700°C for 4 hours to obtain the composite oxide.

[0089] Comparative Example 1

[0090] A nano cerium zirconium oxide, the preparation process is as follows:

[0091] Step A is the same as step A of the embodiment.

[0092] B. Firstly, dissolve the water-soluble polyamide in deionized water, and then dissolve and disperse the yttrium salt, lanthanum salt, cerium salt and zirconium salt in the polyamide aqueous solution to prepare a PAM-Y / La / Ce / Zr solution.

[0093] C. The alkali solution is titrated at room temperature to react with the PAM-Y / La / Ce / Zr solution to prepare a cerium-zirconium composite hydroxide flocculant solution; after the titration, the solution is aged at 92° C. for 3.5 h; the solution is then cooled to room temperature and filtered to obtain a cerium-zirconium composite hydroxide flocculant.

[0094] Steps D and E are the same as steps D and E of Example 1.

[0095] Comparative Example 2

[0096] A nano cerium zirconium oxide, the preparation process is as follows:

[0097] Step A is the same as step A of the embodiment.

[0098] B. Weigh 20% of the total weight of polyvinyl alcohol in step A and dissolve it in deionized water, then dissolve yttrium salt and lanthanum salt in the polyvinyl alcohol aqueous solution to prepare PVA-Y / La solution. Dissolve cerium salt and zirconium salt in deionized water to prepare Ce / Zr solution.

[0099] C. The Ce / Zr solution and the alkali solution are titrated at room temperature to react with the PVA-Y / La solution to prepare a cerium-zirconium composite hydroxide flocculant solution; after the titration, the solution is aged at 92°C for 3.5h; the solution is then cooled to room temperature and allowed to stand for 4 days, and the cerium-zirconium composite hydroxide flocculants are separated by filtration.

[0100] Steps D and E are the same as steps D and E of Example 1.

[0101] Comparative Example 3

[0102] A nano cerium zirconium oxide, the preparation process is as follows:

[0103] A. Weigh the corresponding weights of soluble cerium salt (cerium nitrate), soluble zirconium salt (cerium nitrate), soluble yttrium salt (yttrium nitrate), and soluble lanthanum salt (lanthanum nitrate) according to the molar ratio of metal elements of 22:40:2:1.

[0104] Steps B, C, D, and E are the same as steps B, C, D, and E of Example 1.

[0105] The performance of the nano-cerium zirconium oxide provided in each embodiment and comparative example was tested, and the results are shown in the following table:

[0106]

[0107] It can be seen from the above table that the nano cerium-zirconium oxide provided by the embodiment of the present application has higher thermal stability, larger surface area and smaller particle size.

[0108] It can be seen from the test data of Example 1 and Comparative Example 1 that by using water-soluble polyamide as an auxiliary adsorption material and utilizing its coordination adsorption effect on rare earth metal cations, rare earth metal cations with a low content are first captured to form a PAM-Y / La metal complex, and then secondary adsorbed to form Ce and Zr hydroxide colloids, thereby improving the dispersibility of rare earth metal elements in the final product and enhancing the high-temperature thermal stability of the final product.

[0109] It can be seen from the test data of Example 1 and Comparative Example 2 that the polyvinyl alcohol used as the auxiliary adsorption and dispersion material and the presence of both hydrophilic groups and hydrophobic groups in the water-soluble PAM molecules can reduce the water surface tension, improve the dispersibility of the hydroxide colloid in the precipitated flocculent, and reduce the reduction in specific surface area caused by agglomeration; at the same time, the network structure formed between the PAM molecular chains helps to protect the colloid, and to a certain extent can slow down the collapse of the crystal pore structure caused by water loss during the high-temperature calcination of the hydroxide colloid into an oxide, resulting in a reduction in surface area and pore size, thereby obtaining a cerium zirconium oxide product with a larger surface area and a smaller particle size.

[0110] It can be seen from the test data of Example 1 and Comparative Example 3 that the heat aging resistance of the cerium zirconium oxide product decreases significantly when the proportion of yttrium salt and lanthanum salt in the feed ratio is reduced. This is because the yttrium and lanthanum rare earth elements can effectively stabilize the phase structure of the cerium zirconium oxide product, reduce the sintering rate of the material, and improve the thermal stability.

[0111] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0112] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can both mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b and c can be single or multiple.

[0113] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing nano cerium zirconium oxide, characterized in that: The method comprises: obtaining an auxiliary adsorption material solution, wherein the auxiliary adsorption material comprises polyamide; Dispersing a rare earth element salt in the auxiliary adsorption material solution to obtain a first solution; reacting a mixed solution of cerium salt and zirconium salt, an alkali solution and the first solution to obtain cerium-zirconium composite hydroxide floccules; The cerium-zirconium composite hydroxide floccules are baked and calcined to obtain nano-cerium-zirconium oxide.

2. The method for preparing nano cerium-zirconium oxide according to claim 1, characterized in that: The polyamide includes anionic polyamide.

3. The method for preparing nano cerium-zirconium oxide according to claim 1, characterized in that: The mass concentration of the auxiliary adsorption material in the auxiliary adsorption material solution is 0.2% to 0.5%.

4. The method for preparing nano cerium-zirconium oxide according to claim 1, characterized in that: The rare earth element salts include yttrium salts and lanthanum salts.

5. The method for preparing nano cerium-zirconium oxide according to claim 4, characterized in that: The yttrium salt comprises yttrium nitrate; and / or The lanthanum salt comprises lanthanum nitrate; and / or The cerium salt comprises cerium nitrate; and / or The zirconium salt comprises zirconium nitrate; and / or The molar ratio of the metal elements Ce, Zr, Y and La in the cerium salt, zirconium salt, yttrium salt and lanthanum salt is (22-24): (40-42): (4-5): (2-3).

6. The method for preparing nano cerium-zirconium oxide according to claim 4, characterized in that: The total mass concentration of the metal elements Y and La in the first solution is 1% to 2%; and / or The total mass concentration of the metal elements Ce and Zr in the mixed solution of the cerium salt and the zirconium salt is 10% to 20%.

7. The method for preparing nano cerium-zirconium oxide according to claim 1, characterized in that: The alkali solution comprises at least one of an aqueous ammonia solution and an alkali metal solution; and / or The mixing reaction is carried out by titration; and / or The pH value of the whole system during the mixed reaction is 8.5 to 9.5; and / or The volume of the mixed solution of cerium salt and zirconium salt is 10 to 20 times the volume of the first solution.

8. A nano cerium-zirconium oxide, characterized in that: The nano cerium zirconium oxide is prepared by the method according to any one of claims 1 to 7.

9. The nano cerium-zirconium oxide according to claim 1, characterized in that: The nano cerium zirconium oxide comprises CeO2, ZrO2, Y2O3 and La2O3, and the mass ratio of CeO2, ZrO2, Y2O3 and La2O3 is (35-45): (45-55): (5-10): (5-10).

10. A three-way catalyst, characterized in that: The three-way catalyst comprises a catalytic coating, and the catalytic coating comprises the nano cerium-zirconium oxide according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Porous yttrium-cerium-zirconium solid solution and preparation method thereof

    CN101637721B

  • Nano cerium-and-zirconium-based solid solution rare earth oxygen storage material and preparation method thereof

    CN102407100B

  • Composite oxides and their preparation methods

    CN106824163B

  • Oxygen storage materials, their preparation methods and applications

    CN108970602B